Interlaboratory comparison of relative humidity standards among Latin American National Metrology Institutes (SIM.T-S10) - Brionizio, J D; Mendoza, J; Zapata, D; Armijos, D; Sánchez, C; Bohórquez, A; Riveros, A; Castro, F; Marchant, M E; Skabar, J G; Sica, A; Robatto, O; et al. (IOP Publishing, 2021)
Main text This report presents the results of a comparison in the context of an international collaboration that gives confidence in the relative humidity measurements carried out by several Latin-American institutes within the Mutual Recognition Arrangement (MRA) of the International Committee on Weights and Measures (CIPM). This interlaboratory comparison of humidity standards, the first one in Latin-America and one of the few of this type in the world, was organized in two rounds and carried out by the following National Metrology Institutes: INMETRO (Brazil), IBMETRO (Bolivia), INEN (Ecuador), INM (Colombia), CENAMEP AIP (Panama), ENAER (Chile), INTI (Argentina), LATU (Uruguay) and INTN (Paraguay). The interlaboratory comparison was performed in the scope of relative humidity in the range from 30 %rh to 90 %rh at temperatures of 20 °C and 40 °C. In this comparison, INMETRO was the reference laboratory, and acted as coordinator together with IBMETRO. Two thermohygrometers with capacitive humidity sensors were used as transfer standards, which were calibrated three times by the reference laboratory during the course of the interlaboratory comparison. A technical protocol prepared by INMETRO and IBMETRO circulated among the participants for comments. To sum up, the participants used their own calibration procedures for calibrating the transfer standards together with some instructions given in the technical protocol. Besides, the participants had to submit with the measurement results the respective uncertainties estimated according to their internal procedures and the Guide to the Expression of Uncertainty in Measurement (GUM). The performance of each participating laboratory was evaluated by comparing its measurements results with those of the reference laboratory by means of the normalized error, according to ISO/IEC 17043:2010, and by the degree of equivalence. To reach the main text of this paper, click on Final Report . Note that this text is that which appears in Appendix B of the BIPM key comparison database https://www.bipm.org/kcdb/ . The final report has been peer-reviewed and approved for publication by the CCT, according to the provisions of the CIPM Mutual Recognition Arrangement (CIPM MRA).